Perkawinan Adat “Rasan Jahat” Perspektif Maqashid Syariah (Studi Desa Sako Kecamatan Rambutan Kabupaten Banyuasin) - Mawardi, Muhammad Afiq Zamzami; Rochmiyatun, Siti; Azhari, Ari; Fani, Khairul (UIN Fatmawati Sukarno Bengkulu, 2025)
: Marriage for Muslims is something that is very sacred and has a sacred purpose and cannot be separated from the provisions stipulated by Islamic law. The existence of customary marriage regulations between one indigenous community and another, with differences in these customary regulations, often resolves inter-customary marriages into protracted problems. Sako Village, Rambutan District, Banyuasin Regency has Sako Village Regulation Number 05 of 2014 concerning the Existence of Traditional Law Communities and the Compilation of Sako Village Customs. In one of the chapters discussing traditional marriages, the village regulations explain that there are 2 types of marriage feelings, one of which is